Induced cytotoxicity of peptides with crypto-thioester through native chemical ligation. (27th January 2023) - Lee, Jeonghun; Oh, Eun-Taex; Kim, Jinhyeok; Kim, Kitae; Park, Heon Joo; Kim, Chulhee
Abstract : For induced cytotoxicity, peptide fragments with low cytotoxicity were prepared, which can be coupled to form cytotoxic KLA peptide derivatives through native chemical ligation in reducing environments. Abstract : KLA is an antimicrobial helical peptide that can disrupt cellular membranes by forming a helical pore. The peptide KLA has been adopted as a therapeutic agent for cancer cells. However, the biomedical applications of KLA peptide are limited owing to its low selectivity. Here, to control the bioactivity, two pairs of KLA fragments that contain protected thiol groups with low cytotoxicity and helicity are prepared. These peptide fragments are coupled to form cytotoxic KLA peptide derivatives through native chemical ligation (NCL), which is a coupling reaction between two peptides (containing a C-terminal thioester group and an N-terminal cysteine unit) to form a single peptide connected by a native amide bond. NCL in a reducing environment results in KLA peptide derivatives with greater cytotoxicity and helicity compared with the peptide fragments. Furthermore, the change in cytotoxicity before and after the NCL reaction is dependent on the position of peptide fragmentation. These results provide a valuable route to preparing therapeutic peptide fragments with cytotoxicity induced by NCL on the desired target cells – such as malignant cancer cells – in reducing environments.